Immunoenhancement effects of pentadecapeptide derived from Cyclina sinensis on immune-deficient mice induced by Cyclophosphamide. (September 2019) - Yu, Fangmiao; Zhang, Zhuangwei; Ye, Shengwang; Hong, Xiaoxia; Jin, Huoxi; Huang, Fangfang; Yang, Zuisu; Tang, Yunping; Chen, Yan; Ding, Guofang
Graphical abstract: Highlights: The immunomodulatory properties of the peptide SCSP in vivo were investigated. SCSP restored bodyweight and organ index and enhanced TNF-α release in vivo . SCSP improved specific cellular immune function (DTH and CD4 + /CD8 + ) in vivo . SCSP enhanced humoral immune function (Ig and HC50 ) in immunocompromized mice. Abstract: The immunopotentiating effects of SCSP, a novel pentadecapeptide (RVAPEEHPVEGRYLV) purified from protein hydrolysates of Cyclina sinensis, have been demonstrated in RAW264.7 cells in vitro . In this study, the in vivo effects of SCSP were investigated in an immunosuppressed mouse model generated by administration of CTX. SCSP treatment increased the bodyweight of immunosuppressed mice increased in a dose-dependent manner, remarkably increased the spleen and thymus indexes, and alleviated the pathological features of immune organs. SCSP treatment also upregulated serum TNF-α levels in a dose-dependent manner and significantly restored DTH in CTX-induced immunosuppressed mice. Moreover, CD3 + and CD4 + T lymphocyte counts were dose-dependently elevated and the CD4 + /CD8 + ratio was restored and the serum levels of IgA, IgG, IgM and serum hemolysin were significantly increased by SCSP. These findings further demonstrate that SCSP is an effective immunomodulator with potential for use as the basis for development of functional foods or dietary supplements.